(untitled) - Hyland, Ken (London, 2006)
This book "introduces the major theories, approaches and controversies in the field. [It] gathers together influential readings from key names in the discipline, including: John Swales, Alastair Pennycook, Greg Myers, Brian Street and Ann Johns. [It] provides numerous exercises as practical study tools that encourage in students a critical approach to the subject. Written by an experienced teacher and researcher in the field, 'English for academic purposes' is an essential resource for students and researchers of applied linguisitics."
Keywords: English language,Tiếng Anh; Foreign speakers,Study and teaching,Nói ngoại ngữ,Dạy và học